The using of impulse methods of influence for production of cast articles from aluminium alloys - A. A. Andrushevich; I. N. Kazanevskaja; M. N. Churic (Литьë и металлургия)
In the article there are examined the problems of using of impulse processing of different intensity for production of cast articles from aluminium alloys.